Оцінка фізичної підготовленості в системі професійно-прикладної фізичної підготовки студенток медичних вищих навчальних закладів - Сазанова, Інна Олексіївна; Дорошенко, Едуард Юрійович; Sazanova, I. O.; Doroshenko, E. Yu. (My University, 2018)
В статті на матеріалах оцінювання рівня фізичної підготовленості студенток 1-2 курсів медичних і фармацевтичних факультетів Запорізького державного медичного університету проаналізовано динаміку рівня фізичної підготовленості та розглянуто можливості використання цих показників в системі професійно-прикладної фізичної підготовки. Preparation for future professional activities includes not only the acquisition of relevant knowledge, skills and abilities in the chosen specialty, but also requires some physical training that provides high productivity. Specialist in medical (pharmaceutical) profile for qualitative performance of production duties should be optimal or close to optimal levels of health, physical fitness and physical development. The students of higher bulk establishments have trouble moments associated with reduced levels of health and physical fitness due to hypodynamia, inappropriate nutrition and lifestyle. The dynamics of the level of physical preparedness and the possibilities of using these indicators in the system of professional and applied physical training are analyzed in the article on the materials of assessment of the level of physical fitness of students 1-2 courses of medical and pharmaceutical faculties of Zaporizhzhya State Medical University. The assessment of the level of physical fitness of students of 1-2-courses indicates the tendency toward higher indicators, according to estimates of the manifestation of flexibility and coordination abilities and, accordingly, significantly lower indicators of the level of development of power, speed capabilities and overall endurance. Despite the rather high level of coverage of the issues of physical fitness of students, it remains unresolved the problem of the formation of the system of professional and applied physical training of students of medical higher educational institutions, in which the leading place is the improvement of the level of physical preparedness and the appropriate orientation of the use of physical education to the requirements of a specific profession of the future medical worker.
Assessment of Physical Fitness in the System of Professional and Applied Physical Training of Students of Medical Higher Educational Institutions
Keywords: оцінка; рівень; студентки; професійно-прикладна фізична підготовка; результат; динаміка; показник; assessment; level; students; professional-applied physical training; result; dynamics; index